A systematic review and meta‐analysis of the association between personality and cognitive failures/complaints. Issue 11 (30th September 2020) - Aschwanden, Damaris; Sutin, Angelina R.; Luchetti, Martina; Allemand, Mathias; Stephan, Yannick; Terracciano, Antonio
Abstract: This systematic review examined the associations of personality traits with cognitive failures and cognitive complaints across the adult lifespan. We first present three conceptual models (cognitive abilities, mental processes, and reporting bias) that could explain why personality is related to such behaviors. We then conducted five separate meta‐analyses with 10–17 cross‐sectional samples ( N = 7, 642 – 10, 564) that were identified through a systematic literature search following the MOOSE guidelines. Higher neuroticism ( r = .39, 95% CI [0.32, 0.45]) and lower conscientiousness ( r = −.36, 95% CI [−.42, −.29]) were related to more cognitive failures and complaints. Lower scores on the remaining traits were also associated with more cognitive failures and complaints, yet to a weaker extent (extraversion: r = −.14, 95% CI [−.20, −.08]; openness: r = −.07, 95% CI [−.11, −.03]; agreeableness: r = −.13, 95% CI [−.21, −.05]). With the current empirical evidence, it is not possible to tell which of the three conceptual models explains how much of the associations. For neuroticism, there is more support for the mental processes than the reporting bias model, but more research is needed to fully test mechanistic models. We provide several suggestions for future research to address existing limitations of the literature on personality and cognitive failures and complaints.